Exploring Attitudes of Mandatory Volunteers: The Role of Perceived Organizational Support, Role Clarity, and Self-Efficacy Toward Service. (April 2023) - Bang, Hyejin; Lee, Cindy; Won, Doyeon; Chiu, Weisheng; Chen, Lei
This study attempted to investigate the effects of perceived organizational support (POS) and role clarity on volunteer satisfaction, the mediating role of attitudes toward volunteering in the relationship between volunteer satisfaction and attitudes toward civic participation, and the moderating role of self-efficacy toward service in the relationships between POS, role clarity, and volunteer satisfaction among mandatory volunteers. Using data conducted at a major event in Wuhan, China, results showed that POS and role clarity predicted volunteer satisfaction. Volunteer satisfaction positively influenced attitudes toward volunteering, which is linked to attitudes toward civic participation. Self-efficacy toward service moderated the associations between POS, role clarity, and volunteer satisfaction, highlighting its essential role in strengthening the effects of organizational climate factors on volunteer satisfaction. Our findings underline the important role of organizations in increasing mandatory volunteers' satisfaction that affects positive attitudes toward volunteering, leading to enhanced attitudes toward civic participation.